2022
DOI: 10.3389/fonc.2022.813242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Efficacy Between Transabdominal and Transthoracic Surgical Approaches for Siewert Type II Adenocarcinoma of the Esophagogastric Junction: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe optimal surgical approach, whether transabdominal (TA) or transthoracic (TT), for Siewert type II adenocarcinoma of the esophagogastric junction (AEG) remains controversial. This study compares the efficacy of TA and TT surgical approaches for Siewert type II AEG.MethodsStudies comparing the surgical and oncological outcomes of TA and TT surgical approaches for Siewert type II AEG up to June 2021 were systematically searched on the Web of Science, PubMed, Embase, and Cochrane Library. A pooled an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…At present, radical gastrectomy combined with D2 lymphadenectomy is still the most effective treatment for GC (2,3). The status of lymph nodes (LNs) is a stronger prognostic factor for the survival of GC patients and sufficient lymphadenectomy can improve the prognosis of GC patients (4)(5)(6). Howerer, lymphadenectomy for GC is usually performed without the aid of visual instruments and complete lymphadenectomy is sometimes difficult, especially for inexperienced gastrointestinal surgeons, which always results in LNs residue and in turn leads to tumor recurrence as well as the death of these patient.…”
Section: Introductionmentioning
confidence: 99%
“…At present, radical gastrectomy combined with D2 lymphadenectomy is still the most effective treatment for GC (2,3). The status of lymph nodes (LNs) is a stronger prognostic factor for the survival of GC patients and sufficient lymphadenectomy can improve the prognosis of GC patients (4)(5)(6). Howerer, lymphadenectomy for GC is usually performed without the aid of visual instruments and complete lymphadenectomy is sometimes difficult, especially for inexperienced gastrointestinal surgeons, which always results in LNs residue and in turn leads to tumor recurrence as well as the death of these patient.…”
Section: Introductionmentioning
confidence: 99%
“…A multicenter study with 260 patients showed a survival benefit for THG versus TTE, possibly due to more cT1 stages in the THG group 37 . Last year, a meta-analysis of 12 studies showed no differences between both approaches, including patients as long ago as 1985, therefore not reflecting current standards 38 …”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have been conducted with the aim of identifying the optimal surgical resection type; however, ultimately, no particular approach has demonstrated superiority. 25,28,29 Instead, surgical planning should be guided by aiming to achieve the aforementioned tenets of obtaining a margin-negative resection with safe reconstruction and complete oncologic lymphadenectomy. In addition, there appear to be clear benefits to performing resection using minimally invasive techniques-as opposed open surgerywhen this is technically feasible.…”
Section: Surgical Approachmentioning
confidence: 99%
“…Potential options for resection include total gastrectomy, proximal gastrectomy, and esophagectomy. Multiple studies have been conducted with the aim of identifying the optimal surgical resection type; however, ultimately, no particular approach has demonstrated superiority 25,28,29 . Instead, surgical planning should be guided by aiming to achieve the aforementioned tenets of obtaining a margin‐negative resection with safe reconstruction and complete oncologic lymphadenectomy.…”
Section: Case Presentationmentioning
confidence: 99%